Psychological Interventions for Frontliners in A Malaysian Teaching Hospital : A Brief Narrative Report - Nur Iwana, Abdul Taib; Luke, S.C.W; NIK RUZYANEI, NJ; HAJAR, MSS; WAI WAI, Y.; CHOON LENG, E.; SURIATI, M.S; WAN SALWINA, W.I.; MARHANI, M. (2022)
Introduction: In the wake of the COVID-19 pandemic, Malaysia implemented a Movement Control Order (MCO) beginning on 18th March 2020. Since then, Hospital Canselor Tuanku Muhriz (HCTM) became one of the main hospitals for treating COVID-19 patients in Malaysia. Considering the increasing need for psychological support by frontliners, the Psychiatry Department of HCTM initiated multiple mental health programs during the MCO period. Objective: This study aimed to describe the different psychological interventions and evaluate the effects of relaxation technique sessions to mitigate the psychological impact of the recent COVID-19 outbreak on medical professionals and health care workers (doctors, nurses, allied health workers, lab technicians) in UKM Medical Centre. Methods: The Psychiatry Department of HCTM released three digital mental health initiatives namely the Psychological Support Guide electronic booklet, a portal (www.tabah.my) and the Illness Recovery & Self-Management (IRYS) chatbot on April 2020. A psychological first aid (PFA) hotline and an outreach programme for the Emergency Department and Operation Room staff were also provided. During the outreach programme, the participants were evaluated using the Kessler Psychological Distress Scale (K10) and the Mindful Attention Awareness Scale (MAAS) questionnaires before and after the intervention. Results: Among the 61 participants, the MAAS scores improved after the programme. In the matched pre- and post-test sample (N=13), the relaxation technique sessions showed statistically significant increase in MAAS scores (Z = -2.695, p = 0.007). The median post-test MAAS score was 4.8 compared with 4.1 for the pre-test. Conclusions: The study suggested that hospital staff appreciated mindfulness better after the outreach session. The pandemic provides an opportunity to explore the use of digital technology to further expand our mental health outreach initiatives, but further studies will be required to properly analyse the effectiveness of these interventions and services.